2006
DOI: 10.1007/s00253-005-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression and bulk crystallization of recombinant l-methionine γ-lyase, an anticancer agent

Abstract: L-Methionine gamma-lyase is a pyridoxal 5'-phosphate-dependent enzyme which has tumor selective anticancer activity. An efficient production process for the recombinant enzyme was constructed by using the overexpression plasmid in Escherichia coli, large-scale cultivation, and practical crystallization on an industrial scale. The plasmid was optimized with a promoter and the region of the ribosome-binding site. Plasmid pMGLTrc03, which has a trc promoter and a spacing of 12 nucleotides between the Shine-Dalgar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 31 publications
2
55
0
Order By: Relevance
“…The culture broth was transferred to 1.6 liter of fermentation medium (1.2% bacto tryptone, 2.4% bacto yeast extract, 2.0% glycerol, 1.25% K 2 HPO 4 , 0.23% KH 2 PO 4 , 0.05% polypropylene glycol no. 2000, and 10 mg/ml, tetracycline hydrochloride, pH 7.4) and cultivated at 28 C for 18 h with shaking. For expression of the recombinant MGL Pp, isopropyl--D-thiogalactopyranoside was added at a final concentration of 1 mM after cultivation for 4 h. The concentrated cell suspension was diluted with 50 mM potassium phosphate buffer (pH 7.2) containing 1 mM EDTA, 0.5 mM PLP, 0.01% dithiothreitol, and 1 mM PMSF.…”
Section: Methodsmentioning
confidence: 99%
“…The culture broth was transferred to 1.6 liter of fermentation medium (1.2% bacto tryptone, 2.4% bacto yeast extract, 2.0% glycerol, 1.25% K 2 HPO 4 , 0.23% KH 2 PO 4 , 0.05% polypropylene glycol no. 2000, and 10 mg/ml, tetracycline hydrochloride, pH 7.4) and cultivated at 28 C for 18 h with shaking. For expression of the recombinant MGL Pp, isopropyl--D-thiogalactopyranoside was added at a final concentration of 1 mM after cultivation for 4 h. The concentrated cell suspension was diluted with 50 mM potassium phosphate buffer (pH 7.2) containing 1 mM EDTA, 0.5 mM PLP, 0.01% dithiothreitol, and 1 mM PMSF.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, depletion of L-methionine is effective for cancer therapy. The therapeutically utility of the enzyme for depleting L-methionine has been reported (2). The enzyme has been found to be an effective anti-tumor agent in vitro and in vivo and to be of potential value in the treatment of Parkinson's disease, arteriosclerosis, aging and obesity (9).…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor efficacy of MGL, which is based on the greater L-methionine dependency of cancer cells for growth compared to normal cells has been investigated (3). Many human cancer cell lines and primary tumors have an absolute requirement for L-methionine, an essential amino acid (2). In vitro studies have demonstrated that several murine and human tumor cell lines need exogenous methionine to survive and proliferate (12).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations